Lipocalin-2 Alleviates LPS-Induced Inflammation Through Alteration of Macrophage Properties - Du H; Liang L; Li J; Xiong Q; Yu X; Yu H (Dove Medical Press, 2021)
Huahua Du,1 Li Liang,1 Jiahui Li,1 Qingqing Xiong,1 Xin Yu,2 Hong Yu3 1MoE Key Laboratory of Molecular Animal Nutrition, College of Animal Science, Zhejiang University, Zhejiang, 310058, People's Republic of China; 2Department of Anesthesia, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, Zhejiang, 310016, People's Republic of China; 3Department of General Surgery, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, Zhejiang, 310016, People's Republic of ChinaCorrespondence: Hong YuDepartment of General Surgery, Sir Run Run Shaw Hospital, School of Medicine, Zhejiang University, Zhejiang, 310016, People's Republic of ChinaTel +86-571-86044817Fax +86-571-86090063Email blueyu000@zju.edu.cnPurpose: Lipocalin-2 (Lcn2) is an acute-phase protein and elevated in several inflammatory diseases. This study aimed to determine whether Lcn2 alleviates inflammation and explore the underlying cellular mechanisms.Methods: C57BL/6 Lcn2-deficient (Lcn2−/-) male mice were intraperitoneally injected with lipopolysaccharide (LPS) to build systemic inflammation model. The inflammatory processes were investigated. The morphology of villi was measured by scanning electron microscopy (SEM). The levels of inflammatory factors were detected by ELISA and qPCR analysis. The production of Lcn2 was determined with immunofluorescence staining by confocal microscope. The molecular mechanism of Lcn2 in bone marrow-derived macrophages (BMDMs) was analyzed by mass spectrometry (MS)-based quantitative proteomic analysis.Results: Compared to wild-type (WT) mice injected with LPS, Lcn2−/- mice injected with LPS showed increased inflammatory damage in jejunum and ileum, and significantly elevated the levels of multiple pro-inflammatory cytokines. After determining that Lcn2 was mainly located in the cytoplasm of macrophages, we isolated BMDMs from Lcn2−/- mice to evaluate their function. During LPS challenge, transcripts of pro-inflammatory cytokines were all significantly increased in BMDMs from Lcn2−/- mice, while those of anti-inflammatory cytokines were significantly decreased when compared with the cytokines in BMDMs from WT mice. A label-free relative quantitation proteomics analysis showed that LPS-treated BMDMs from Lcn2−/- mice had elevated levels of pro-inflammatory pathways, but reduced phagocytosis and autophagy when compared with LPS-treated BMDMs from WT mice.Conclusion: These findings demonstrated that Lcn2 was a potent protective factor in response to systemic inflammation and might be an indispensable factor for macrophage functions.Keywords: Lcn2, systemic inflammation, macrophages, BMDMs